Evaluating the Relation between Personality Properties with Job Satisfaction of the Staff - Golpayegan, Maryam Alvankar (Journal of History Culture and Art Research, 2017)
In any organization, any individual’s organizational role should be coordinated with his individual personality in order for the individual behavior to be coordinated with organizational behavior and in order for the organization’s life not to be disturbed in the case of lack of authenticity between individual personality with organizational role so that the members of organization may get in to trouble influenced by such a conflict and be inevitable before the organization. The aim of this research is evaluating the relation between personality properties with job satisfaction of the staff. The current research method is descriptive correlation. Statistical society of the present research were all staff of a governmental organization in Tehran city. Research sample was 80 people who were chosen through random sampling. Finally, in order for analysis of the data, SPSS software was used. The results of this research showed that there was a significant relation and positive correlation between introversion personality type with the extent of job satisfaction and also there was a negative and significant relation between two variables of extroversion personality type with job satisfaction. On the other hand, considering personality dimensions of the individuals in the organization is among the categories that has an efficient role in progress and health improvement of workforce.